Theoretical models of anti-diffusion layers of ternary Fe-Ni-W systems in thermoelectric energy converters - Manyk, O.M.; Krechun, M.M.; Razinkov, V.V. (Journal of Thermoelectricity, 2025)
Theoretical models were developed and calculations of the chemical bond parameters of promising antidiffusion layers based on ternary systems Fe-Ni-W were performed. Calculations of the effective radii of interatomic interaction, redistribution of electron density and energy of nonequivalent chemical bonds Fe-Ni, Fe-W, Ni-W in the Fe-Ni-W system depending on the interatomic distances were presented.